Pharmacophore-based virtual screening, synthesis, biological evaluation, and molecular docking study of novel pyrrolizines bearing urea/thiourea moieties with potential cytotoxicity and CDK inhibitory activities - Ahmed M. Shawky; Nashwa A. Ibrahim; Mohammed A. S. Abourehab; Ashraf N. Abdalla; Ahmed M. Gouda (Taylor & Francis Group, 2021)
In the current study, virtual screening of a small library of 1302 pyrrolizines bearing urea/thiourea moieties was performed. The top-scoring hits were synthesised and evaluated for their cytotoxicity against three cancer (MCF-7, A2780, and HT29) and one normal (MRC-5) cell lines. The results of the MTT assay revealed potent cytotoxic activities for most of the new compounds (IC50 = 0.16-34.13 μM). The drug-likeness study revealed that all the new compounds conform to Lipinski's rule. Mechanistic studies of compounds 18 b, 19a, and 20a revealed the induction of apoptosis and cell cycle arrest at the G1 phase in MCF-7 cells. The three compounds also displayed potent inhibitory activity against CDK-2 (IC50 = 25.53-115.30 nM). Moreover, the docking study revealed a nice fitting of compound 19a into the active sites of CDK-2/6/9. These preliminary results suggested that compound 19a could serve as a promising scaffold in the discovery of new potent anticancer agents.